Failure Analysis Fundamentals and Applications in Mechanical Components - Otegui, Jose Luis.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book addresses the failures of structural elements, i.e. those components whose primary mission is to withstand mechanical loads. The book is intended as a self-contained source for those with different technical grades, engineers and scientists but also technicians in the field can benefit from its reading.
Introduction -- Tools for Preliminary Analysis of a Mechanical Failure -- Tools for the Microscopic Analysis of a Mechanical Failure -- Damage and Failure Mechanisms -- Characterization and Testing of Materials -- Mechanical Modelling Tools applied to Failure Analysis -- Root Cause Analysis -- Damage and Failure Mechanisms in Machinery -- Mitigation and Life Prediction -- Consequences of a Failure Analysis.
Keywords: Engineering; Materials; Mechanical engineering; Building construction; Surfaces (Physics).; Engineering; Mechanical Engineering; Continuum Mechanics and Mechanics of Materials; Characterization and Evaluation of Materials; Building Repair and Maintenance